Comparison of Success Rates between Buccal Mucosal Graft and Penile Skin Graft in Anterior Urethral Stricture Repair: A Systematic Review - Mochammad Haikal Alhamdi (SCRIPTA SCORE Scientific Medical Journal, 2026)
Background: Anterior urethral stricture is a common urologic condition that may require substitution urethroplasty when endoscopic treatment fails. Buccal mucosal graft (BMG) and penile skin graft/flap (PSG/PSF) are established options, but their comparative success remains debated. Objective: To compare the success and safety outcomes of BMG and PSG/PSF urethroplasty in adult males with anterior urethral stricture. Methods: A systematic review was conducted following PRISMA 2020 guidelines. Databases searched included PubMed, Embase, Scopus, Web of Science, and Cochrane Library for studies published between 2015 and 2025. Randomized controlled trials, comparative cohorts, and meta-analyses evaluating BMG versus PSG/PSF urethroplasty were included. Twelve studies met inclusion criteria and were analyzed narratively. Results: Both graft types showed comparable success and stricture-free rates (85–94%) with no significant difference in recurrence or urinary flow improvement. BMG was favored in patients with lichen sclerosus due to resistance to dermal inflammation, whereas PSG/PSF was suitable when oral harvest was contraindicated. Donor-site morbidity was mild and self-limiting in both groups. Conclusion: Buccal mucosal and penile skin graft urethroplasty yield equivalent outcomes in anterior urethral stricture repair. Graft selection should be individualized based on patient condition and surgeon expertise. Further multicentre randomized studies with standardized outcome definitions are required to confirm long-term differences. Keywords: anterior urethral stricture, buccal mucosal graft, penile skin graft, urethroplasty, reconstruction surgery. Latar Belakang: Striktur uretra anterior merupakan kelainan urologis yang memerlukan urethroplasty substitusi bila terapi endoskopi gagal. Cangkok mukosa bukal (BMG) dan cangkok kulit penis (PSG/PSF) merupakan pilihan utama, namun perbandingan keberhasilannya masih diperdebatkan. Tujuan: Membandingkan keberhasilan dan keamanan urethroplasty menggunakan BMG dan PSG/PSF pada pria dewasa dengan striktur uretra anterior. Metode: Tinjauan sistematik dilakukan berdasarkan pedoman PRISMA 2020. Basis data PubMed, Embase, Scopus, Web of Science, dan Cochrane Library ditelusuri untuk publikasi tahun 2015–2025. Studi acak terkontrol, kohort komparatif, dan meta-analisis yang menilai BMG versus PSG/PSF disertakan. Sebanyak dua belas studi memenuhi kriteria inklusi dan dianalisis secara naratif. Hasil: Kedua jenis cangkok menunjukkan tingkat keberhasilan dan bebas striktur serupa (85–94%) tanpa perbedaan bermakna pada angka kekambuhan atau peningkatan aliran urin. BMG lebih unggul pada kasus dengan lichen sclerosus, sedangkan PSG/PSF sesuai untuk pasien yang tidak dapat dilakukan pengambilan mukosa oral. Morbiditas donor ringan dan bersifat sementara. Kesimpulan: Cangkok mukosa bukal dan kulit penis memberikan hasil yang sebanding pada rekonstruksi striktur uretra anterior. Pemilihan cangkok sebaiknya disesuaikan dengan kondisi pasien dan pengalaman operator. Diperlukan penelitian acak multisenter dengan definisi hasil yang terstandar untuk evaluasi jangka panjang. Kata Kunci: bedah rekonstruksi, cangkok mukosa bukal, cangkok kulit penis, striktur uretra anterior, urethroplasty.